La autoría ‘borrosa’ de Herzog & de Meuron y Ai Weiwei en la Serpentine Gallery - López Ujaque, José Manuel (Constelaciones, 2019)
Fue en el verano de 2012 cuando los arquitectos Jacques Herzog y Pierre de Meuron, junto al artista Ai Weiwei, construyeron un pabellón temporal para la Serpentine Gallery de Londres. Su propuesta destacaba por desmarcarse de la imagen de ‘firma’ habitual en este tipo de acontecimientos y por el contrario, acercarse a entendimientos más relacionales y alejados de una noción convencional de la autoría. En realidad, había que hacer muy poco puesto que el proyecto ya existía, tan sólo era necesario hacerlo visible mediante la superposición de las huellas dejadas por los once pabellones de las ediciones previas. Para ello, Ai Weiwei fue de gran ayuda, gracias a su particular manera de entender la historia y los procesos creativos.
The ‘Blurred’ Authorship of Herzog & de Meuron and Ai Weiwei in the Serpentine Gallery
It was in the summer of 2012 when the architects Jacques Herzog and Pierre de Meuron, jointly with the artist Ai Weiwei, constructed the Summer Pavilion of London's Serpentine Gallery. This project stood out for its distinctive character away from traditional 'signature' image in this kind of events and, on the contrary, following a relational approach far from the traditional understanding of authorship. As a matter of fact, very little had to be done as the core of the project already existed, and the objective was to highlight Summer Pavilion's past by efficiently handling the traces and remainings of the pavilions built in the previous eleven editions. Ai Weiwei's contribution was key due to its particular understanding of history and creative processes.
Keywords: memoria; colaboración; automatización; rastros; superponer; relacional Memory; collaboration; automation; traces; superimpose; relational; Emerging